SUSTAINABLE DEVELOPMENT AS THE BASIS FOR ENVIRONMENTAL EDUCATION IN DEVELOPING GREEN SCHOOLS - Qudsi Mutawakil Husaini; Uus Ruswandi; Mohamad Erihadiana (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
This research discusses Sustainable Development as the basis for Environmental Education in developing Green Schools. The method used in this research is library research. The results of this study indicate that the large impact experienced by the environment cannot be separated from globalization. Among the issues in the global world that are currently taking place are extreme climate change, food crises, and economic difficulties that must be faced in today's global world. The environment is very important for human life, therefore preserving it is a form of responsibility for its sustainability for future generations. Schools are one of the tools of society that have a role in integrating the values ??of green education through the application of the Education for Sustainable Development (ESD) method of developing critical thinking and attitude skills in making decisions on issues related to environmental quality both nationally and globally. It is hoped that in addition to successful sustainable development, the quality of the environment will also improve.